Systematic Literature Review: How students learn linear programming with realistic mathematics education? - Octaria, Dina; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra (International Journal of Trends in Mathematics Education Research, 2023)
This study aims to investigate more deeply the material of linear programming with a realistic mathematics education (RME) approach. This research is a literature study with a descriptive qualitative research type with library research using various written sources such as articles from Springer, ScienceDirect, and Google Scholar. This study focuses on the characteristics of RME, the principles of RME, the steps of learning RME on linear programming material, and examples of implementing RME learning on linear programming material. From the results of previous research, it was found that using the RME approach can help students understand linear programming material. This is because real-life problems in linear programming are in line with realistic principles that exist in the RME principle, namely being able to apply mathematics in solving real-life problems and mathematics must start from problem situations that are meaningful for students.